ANALISIS PERTUMBUHAN EKONOMI DI PULAU MADURA - Verawati Fajrin; Heri Sudarsono (Jurnal Ekonomi-Qu, 2019)
This study aims to analyze the effect of government expenditures, household consumption and net exports on economic growth seen from the PDRB of Madura Island which consists of four districts namely Bangkalan, Sampang, Pamekasan, and Sumenep within a period of six years from 2011-2016. The data used in this study were obtained from the Central Statistics Agency (BPS) estimated by panel data regression using the fixed effect method as the best method that resulted in the picture that government expenditures had a significant and negative effect, the household consumption was not significant and positive, net export had a significant effect and positive for gross regional domestic products that have an impact on economic growth on Madura island